Hydropolitics in Central Asia: An analysis of Official and Media Discourses in Kazakhstan and Kyrgyzstan, 2010-2023 - Bekshora, Zh. (International School of Economics Maqsut Narikbayev University, Astana, 2024)
The following study analyzes the hydropolitics between Kazakhstan and Kyrgyzstan through official and media discourses during the four cases spanning the period of 2010-2023. The issue of water resources in Central Asia is highly relevant due to the growing challenges of climate change, poor water management, increasing population, and lack of cooperation in the water sector. The study examines the interesting water relations and power dynamics between downstream Kazakhstan and upstream Kyrgyzstan. The paper uses a qualitative research approach based on discourse analysis. The analysis reveals common narratives of “agriculture-as-a-main-concern” and “good-relations” used in both discourses. Firstly, showing that the main water issue in hydropolitics between Kazakhstan and Kyrgyzstan is agriculture, framing water being used only for irrigation purposes. Secondly, despite the tensions on the water basis, states attempt to avoid politicization of the water and maintain good relations with each other. Moreover, the study shows non-state-centered characteristics of Kazakh-Kyrgyz hydropolitics, incorporating the role of individuals; local citizens. As well as shows the wide range of non-water related issues, such as agriculture, food security, economic interactions, border issues and social discontent. Additionally, the study reveals the power dynamics through hydropolitics, showing that Kyrgyzstan uses water as a leverage, while Kazakhstan imposes the border restrictions to pressure Kyrgyzstan.
Keywords: Hydropolitics in Central Asia, Kazakhstan, Kyrgyzstan